ALKUTURASI NILAI-NILAI ISLAM DAN ADAT KEJAWEN DI DESA MOJOPURO KECAMATAN JATIROTO WONOGIRI - Noor Bekti Negoro; Muhammad Dwiki Dharmawan; Risyanka Nafishafara Irvanti; Zahra Radita Khairunnisa (STKIP Subang, 2026)
This study aims to describe the process of acculturation between Islamic values and Javanese traditional beliefs (Kejawen) that occurs in Mojopuro Village, Jatiroto District, Wonogiri Regency. The research focuses on exploring the forms, supporting factors, and social-spiritual values emerging from the integration of religion and culture. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews with religious and cultural leaders as well as community members, and documentation of socio-religious activities. The findings reveal that the Mojopuro community has successfully integrated Islamic values into Kejawen traditions without creating theological or social conflicts. Local rituals such as selametan, nyadran, and ruwahan continue to be practiced, now enriched with Islamic elements such as the recitation of Yasin and tahlil prayers. Religious leaders play a significant role in this harmonization process through cultural da’wah that adapts Islamic teachings to local traditions. This acculturation fosters values of togetherness, tolerance, mutual cooperation, and respect for ancestors, thereby strengthening social cohesion. The study concludes that Islam can dynamically engage with local culture without losing its essence and contributes to developing a culturally grounded model of Islamic guidance and counseling.